Kontribusi bursa kerja khusus dan kemampuan bekerjasama terhadap kesiapan memasuki dunia kerja siswa sekolah menengah kejuruan - Efrinaldi Efrinaldi; Ambiyar Ambiyar; Hasan Maksum; Waskito Waskito (Jurnal Educatio: Jurnal Pendidikan Indonesia)
The aims of this study are: 1) to find out and analyze the contribution of the special job market to work readiness, 2) to find out and analyze the contribution of the ability to cooperate to work readiness, 3) to know and analyze together the contribution of the special job market and the ability to work together on work readiness. The type of research used is quantitative and uses a descriptive approach. The method used in finding research results is by distributing questionnaires. This research works using three hypotheses: 1) partially there is a positive and significant contribution of the specific job market to work readiness, 2) partially there is a positive and significant contribution of the ability to cooperate to work readiness, 3) jointly there is a positive and significant contribution special job market and the ability to cooperate on job readiness. The research results obtained are: 1) special job fairs have a positive and significant contribution to student work readiness by 31%. This indicates that the better the special job market, the better the student's work readiness and vice versa, 2) the ability to cooperate with students has a positive and significant contribution to student work readiness by 49.3%. Based on these results, it shows that the better the student's collaboration skills, the better the student's work readiness and vice versa. 3) the special job market and the ability to cooperate with students contribute positively and significantly to student work readiness by 49.6%.